Wirtschaftliche Partnerschaftsabkommen (EPAs) der EU mit Afrika: Dominanz der EU Exportinteressen statt Partnerschaft auf Augenhöhe - Dirk Kohnert (ipg-journal: Internationale Politik und Gesellschaft, 2014)
– In view of the global run on African resources the EU is at pains to conclude Economic Partnership Programs with African states up to October 2014. The EPAs are meant not just to liberalize trade but also to promote economic development in Africa and thus creating a win-win situation in a partnership on eye-level. However, many Africans suspect the EU of double talk and of promoting selfish export interest at the expense of inclusive growth in African countries. Taking the proposed ECOWAS EPAs as example, analyses reveal that tensions are due to both the gap between discourse and practice of EU trade and aid policy as well as different hidden interest of different EU directorates and member states. The growing preparedness of African states to challenge EU mercantile interest has been effectively backed by long lasting proactive agitation of NGOs and civil society groups inside and outside Africa. – Compte tenu de la ruée mondiale sur les ressources africaines, l'UE s'efforce de conclure et de créer ainsi une situation gagnant-gagnant dans le cadre d'un partenariat à hauteur d'yeux. Cependant, de nombreux Africains soupçonnent l'UE de tenir un double discours et de promouvoir des intérêts d'exportation égoïstes au détriment d'une croissance inclusive dans les pays africains. Si l'on prend l'exemple des APE proposés par la CEDEAO, les analyses révèlent que les tensions sont dues à la fois à l'écart entre le discours et la pratique de la politique commerciale et d'aide de l'UE, ainsi qu'aux différents intérêts cachés des différentes directions de l'UE et des États membres. La volonté croissante des États africains de contester les intérêts commerciaux de l'UE a été efficacement soutenue par l'agitation proactive de longue durée des ONG et des groupes de la société civile à l'intérieur et à l'extérieur de l'Afrique.
Additional information: Revised author's version of: ,,Afrikas TTIP? Weshalb die EPAs in der jetzigen Form verhindert werden müssen“, published in: Internationale Politik und Gesellschaft (ipg-journal), 4 June 2014
Keywords: F35; F54; H43; N47; Z13; 330; EU; Africa; ACP; ECOWAS; international trade; civic agency